Différence intersexes de la cinétique des acides aminés en réponse à un exercice intermittent long chez des athlètes de haut niveau - Hmani, S.; Adonon, S.; Krichen, M.; Medelli, J. (Science & Sports, 2009)
Study the gender effect in plasmatic concentration of 25 amino acids in high-level athletes after a long intermittent exercise. At the beginning and at the end of exercise amino acids plasmatic concentrations are measured by chromatography.